PENGARUH KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL TERHADAP PRESTASI BELAJAR PADA PESERTA DIDIK - Gregorius Meinanda Eren Praditya; Umbu Tagela; Yustinus Windrawanto (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
Contribution to the academic level of students is influenced not only by intellectual intelligence, spiritual intelligence and emotional intelligence contribute to it. This study aims to determine the effect of emotional intelligence and spiritual intelligence on the learning achievement of class VIII students of SMP Negeri 2 Bringin. This study used a quantitative approach using a comparative causal method. The sample in this study were 72 class VIII students who were determined using a systematic random. Data collection techniques are by using questionnaires and special documentation studies on learning achievement variables. Based on data analysis using multiple linear regression analysis, the results obtained on the partial test that emotional intelligence has no significant effect on student achievement, further from the partial test results the results of the study state that there is a significant influence between Spiritual Intelligence and learning achievement. In the simultaneous processing of data processing it can be stated that there is a significant influence of Spiritual Intelligence and emotional intelligence on student achievement at SMP Negeri 2 Bringin. Data processing regarding the magnitude of the effect can be stated that Emotional Intelligence and Spiritual Intelligence have a contribution to student achievement of 10.5%, while the remaining 89.5% is influenced by other variables not examined.